Konstruksi Klausul Tanggung Jawab Sosial Lingkungan Pada Akta Perubahan Anggaran Dasar Perseroan Terbatas Di Bidang Sumber Daya Alam - Triska Wulan Dari, Nayu (Recital Review, 2023)
Article 74 of the Limited Partnership Act obliges entities that carry out business activities in the field and/or related to natural resources to carry out Social Responsibility for the Environment, where such obligations are estimated and accounted for as expenses of the Association, taking into account consistency and liability. The remuneration is based on the company's work plan in the annual report in the General Meeting of Shareholders, further, Article 1 paragraph (3) of the UUPT states that TJSL is the commitment of the company to participate in the sustainable economic development that is useful to improve the quality of life and the environment that is beneficial for all stakeholders. As such a commitment should the association have the desire to include the wrong clause about TJSL is one of the acts of change of the basic budget of the corporation, although in Article 15 UUPT does not regulate the existence of the component of social responsibility for the environment. The legal issue of this writing is a conflict of norms on the UUPT which states an obligation and forms a commitment, but is not a component in the basic budget of the association. The question is why the TJSL clause is important to be loaded into the act, and how the construction of such a callus, with the aim of knowing the importance and the impact of the callus if loaded in the act of change of the budget of the association. This type of research leads to normative jurisprudence, using legislative approaches, conceptual approaches through primary, skunder, and tertiary legal materials. The results of this research with the loading of the TJSL clause can provide legal certainty in the implementation of obligations, as a reminder (alarm) for the association, and created a legal order, the consequences of TJ SL either incorporated in the matter of earning profits or in a separate article against the act of change of the basic budget either through the party act (the parties) or the Act of Relaas (official report meeting)